Public education in the digital age neoliberalism, EdTech, and the future of our schools - Anderson, Morgan (Routledge, 2023)
Educational technology is now ubiquitous in schooling, both in P-12 and at universities. Despite the imposition of technology in most aspects of teaching and learning, little attention has been given to the implications educational technology has for healthy student development, humane pedagogy, teacher labor, academic freedom, and the aims of social justice. Rather than merely a set of neutral tools, educational technology is bound up with systems of power and privilege that tend to deepen, rather than confront inequality. In calling for a reassessment of the relationship between schools and technology, this book asks readers to think differently about the role technology can serve in socially just schools. An accessible and compelling read, this book will appeal to students and scholars of sociology, social justice, politics, and all those interested in the impact technology is having on the education system in the USA.